Diel migration pattern of pink salmon fry in small streams. Issue 4 (2nd March 2022) - Yamada, Taihei; Urabe, Hirokazu; Nakamura, Futoshi
Abstract: Downstream migration is a critical stage in the anadromous salmonid life cycle, but previous studies have shown different results between rivers or surveys for the diel downstream migration pattern of the fry of the pink salmon Oncorhynchus gorbuscha . We investigated the diel migration pattern of pink salmon fry in three small streams. Our results showed that pink salmon fry migrate mainly within a few hours after sunset; 89.9% of migration occurred between 18:00 and 23:00. Therefore, the results indicated that sunset time influences the diel migration pattern of pink salmon fry in small streams. This pattern could be a predator‐avoidance behaviour.